The Association between Glomerular Diameter and Secondary Focal Segmental Glomerulosclerosis in Chronic Kidney Disease - Ryo Zamami; Kentaro Kohagura; Kojiro Kinjyo; Takuto Nakamura; Takanori Kinjo; Masanobu Yamazato; Akio Ishida; Yusuke Ohya (Karger Publishers, 2021)
Introduction: When nephron loss occurs, the glomerular filtration rate (GFR) is suggested to be maintained by glomerular hypertrophy, but excessive hypertrophy can rather lead to the formation of focal segmental glomerulosclerosis (FSGS), thereby causing progressive kidney damage. However, it is not clear how much glomerular hypertrophy leads to the formation of FSGS. We examined the association between glomerular diameter and FSGS lesions in chronic kidney disease (CKD) patients. Methods: We recruited 77 patients who underwent renal biopsy during 2016-2017; however, those identified with primary FSGS and glomerulonephritis with active glomerular lesion were excluded. We evaluated the maximal glomerular diameter (Max GD), an indicator of glomerular size, in each renal biopsy specimen and examined its association with FSGS lesion. Results: The median age, blood pressure, and estimated GFR of the patients were 53 years, 122/70 mm Hg, and 65 mL/min/1.73 m2, respectively. The optimal cutoff threshold of Max GD for predicting the presence of FSGS lesions, assessed by receiver operating characteristic curve analysis, was determined to be at 224 μm (area under the curve, 0.81; sensitivity, 81%; specificity, 72%). Multivariate logistic regression analyses demonstrated that Max GD ≥224 μm was significantly associated with the presence of FSGS lesions, independent of other confounding factors (odds ratio, 11.70; 95% confidence interval, 1.93-70.84). Discussion/Conclusion: Glomerular hypertrophy (Max GD ≥224 μm) has been associated with FSGS lesions in CKD patients and may reflect the limits of the compensatory process.